2023
DOI: 10.3389/feart.2023.1168384
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative effects of climate change and human activity on the vegetation growth in the Yangtze River Basin

Renjie Guo,
Anning Cai,
Xin Chen

Abstract: Vegetation has changed dramatically in recent years as a result of various disturbances, but the factors influencing vegetation growth vary geographically. We looked into the impact of climate change and human activity on vegetation growth in the Yangtze River Basin (YRB). We characterized vegetation growth in the YRB using gross primary production (GPP) and the leaf area index (LAI), analyzed the relationship between vegetation growth and climate change using the standardized precipitation evapotranspiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…From 1980 to 2022, the lake area of the DBSL decreased, and some vegetation areas near the lake group also experienced varying degrees of degradation. Guo et al [14] studied the interaction between vegetation area and water area changes near Taitema Lake and concluded that vegetation was highly sensitive to water area changes, with a significant decrease in vegetation area in dry years [57]. After the implementation of the ecological water conveyance project, water inflow into the lake increased significantly, and the vegetation area near the lake has generally increased.…”
Section: Dynamic Change Relationship Of the Vegetation-lake-sand Land...mentioning
confidence: 99%
See 1 more Smart Citation
“…From 1980 to 2022, the lake area of the DBSL decreased, and some vegetation areas near the lake group also experienced varying degrees of degradation. Guo et al [14] studied the interaction between vegetation area and water area changes near Taitema Lake and concluded that vegetation was highly sensitive to water area changes, with a significant decrease in vegetation area in dry years [57]. After the implementation of the ecological water conveyance project, water inflow into the lake increased significantly, and the vegetation area near the lake has generally increased.…”
Section: Dynamic Change Relationship Of the Vegetation-lake-sand Land...mentioning
confidence: 99%
“…They play an indispensable role in maintaining the ecological and environmental balance of arid and semi-arid areas [13]. The expansion and shrinkage of lakes affect regional vegetation habitats and determine the distribution pattern of sandy vegetation [14]. Lakes provide conditions for vegetation growth and survival and have an important impact on sand transport [15].…”
Section: Introductionmentioning
confidence: 99%
“…This poses a major challenge to food security in the region. Climate change also promotes vegetation growth in watersheds while inhibiting vegetation growth in other areas [19]. It affects land-use patterns, thereby affecting agricultural and industrial production outcomes in the Huaihe River Basin.…”
Section: Introductionmentioning
confidence: 99%